2016
DOI: 10.1063/1.4948942
|View full text |Cite
|
Sign up to set email alerts
|

Chemical speciation of U, Fe, and Pu in melt glass from nuclear weapons testing

Abstract: Nuclear weapons testing generates large volumes of glassy material that influence the transport of dispersed actinides in the environment and may carry information on the composition of the detonated device. We determine the oxidation state of U and Fe (which is known to buffer the oxidation state of actinide elements and to affect the redox state of groundwater) in samples of melt glass collected from three U.S. nuclear weapons tests. For selected samples, we also determine the coordination geometry of U and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…While the valence state of uranium in the fallout glass during deposition and diffusion is unknown, [93] suggests uranium is present in the hexavalent state in environments of high oxygen fugacity, which is assumed for this study at the temperature and pressure ranges of interest (< 2500 K and ∼ 1 atm, respectively). Further, recent work using x-ray absorption near edge structures (XANES) on melt glass from a uranium-fueled test determined that the uranium predominantly existed in the hexavalent state (i.e., UO 2+ 2 ) [94]. As expected, the equation dictating the temperature dependence of uranium diffusion in this system was found by Mungall to be Arrhenian,…”
Section: Chapter 5 Diffusive Mass Transport In Agglomerates From a Dsupporting
confidence: 56%
See 1 more Smart Citation
“…While the valence state of uranium in the fallout glass during deposition and diffusion is unknown, [93] suggests uranium is present in the hexavalent state in environments of high oxygen fugacity, which is assumed for this study at the temperature and pressure ranges of interest (< 2500 K and ∼ 1 atm, respectively). Further, recent work using x-ray absorption near edge structures (XANES) on melt glass from a uranium-fueled test determined that the uranium predominantly existed in the hexavalent state (i.e., UO 2+ 2 ) [94]. As expected, the equation dictating the temperature dependence of uranium diffusion in this system was found by Mungall to be Arrhenian,…”
Section: Chapter 5 Diffusive Mass Transport In Agglomerates From a Dsupporting
confidence: 56%
“…However, as shown in the recent XANES study of melt glass from near-surface nuclear tests [94], the cooling rate of the fireball (and the carriers entrained in the fireball) can affect the final redox state of the glasses. Thus, the incorporation of xenon isotope precursors (the decay products of fission products) into the volume of molten fallout glasses may have occurred in an earlier, anoxic state, while the deposition layers observed in the agglomerated fallout objects in this study are likely the result of late stage addition in a more oxygenated fireball.…”
Section: Chapter 5 Diffusive Mass Transport In Agglomerates From a Dmentioning
confidence: 99%
“…25,38,41,[57][58][59] A bulk-averaged hard X-ray spectroscopy study of several melt glass samples from historic nuclear tests has been recently reported. 60 Hard X-ray XANES and extended X-ray absorption fine structure (EXAFS) were used to obtain information on the oxidation state and coordination of U and Fe in each sample. Here, Fe is of interest as it is the most concentrated redox-sensitive metal in the samples, and is expected to influence the oxidation states of U and Pu.…”
Section: Melt Glass Speciation With Soft X-ray Stxmmentioning
confidence: 99%
“…[14][15][16][17][18] While X-ray absorption spectroscopy has been applied to a limited number of materials of forensic interest. [19][20][21][22][23] The sensitivity of X-ray absorption near edge structure (XANES) to oxidation state lends itself to the observation of the gradual oxidation of nuclear material due to storage and environmental conditions, [23][24] and to studies of chemical signatures of post-detonation material. [25][26] This article describes the use of scanning transmission X-ray microscopy (STXM) in the soft X-ray region with methods optimized for nondestructive nuclear forensic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…All these tests were conducted in natural and non-urban, remote sites. Despite this large number of tests and the observation that nuclear explosions generate large volumes of glass materials (e.g., Pacold et al, 2016), description of nuclear fallout debris is limited to a few vintage publications (e.g., Adams et al, 1959;Miller, 1964), de-classified studies from USA test sites and recent nuclear forensic studies (e.g., Eppich et al, 2014;Weisz et al, 2017).…”
Section: Nuclear Fallout Debris and The Atomic Explosion At Hiroshimamentioning
confidence: 99%